2008
DOI: 10.1007/s00122-008-0783-6
|View full text |Cite
|
Sign up to set email alerts
|

QTL identification and microphenotype characterisation of the developmentally regulated yellow rust resistance in the UK wheat cultivar Guardian

Abstract: Yellow rust (causal agent: Puccinia striiformis f.sp. tritici) resistance in the UK wheat cultivar Guardian is developmentally regulated, resistance increasing as the plant matures. Yellow rust resistance was assessed under field conditions on plants after ear emergence to ensure maximum expression of resistance. Three quantitative trait loci (QTL) for yellow rust resistance were identified, being located on chromosomes 1B (QPst.jic-1B), 2D (QPst.jic-2D) and 4B (QPst.jic-4B). The largest resistance effect, QPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 27 publications
5
29
0
Order By: Relevance
“…In the current study, six potentially novel QTL for resistance to stripe rust were identified in combined and individual environment analyses (Table 2) and one additional candidate novel QTL was detected exclusively in club wheat (Supplementary Table 10). The novel genomic region identified on 2DS at 28.0 cM is approximately 90–100 cM away from previously reported QTL for stripe rust response on 2DS using bi-parental populations (Bariana et al, 2001; Suenaga et al, 2003; Mallard et al, 2005; Melichar et al, 2008; Lu et al, 2009; Agenbag et al, 2012). Naruoka et al (2015) recently reported a stable APR locus on 2DS (stable in nine environments) using GWA in a winter wheat association panel.…”
Section: Discussionmentioning
confidence: 53%
“…In the current study, six potentially novel QTL for resistance to stripe rust were identified in combined and individual environment analyses (Table 2) and one additional candidate novel QTL was detected exclusively in club wheat (Supplementary Table 10). The novel genomic region identified on 2DS at 28.0 cM is approximately 90–100 cM away from previously reported QTL for stripe rust response on 2DS using bi-parental populations (Bariana et al, 2001; Suenaga et al, 2003; Mallard et al, 2005; Melichar et al, 2008; Lu et al, 2009; Agenbag et al, 2012). Naruoka et al (2015) recently reported a stable APR locus on 2DS (stable in nine environments) using GWA in a winter wheat association panel.…”
Section: Discussionmentioning
confidence: 53%
“…Several temporarily designated Yr genes have been mapped to 1B including: YrAlp [16] and YrC142 [54] on 1BS and YrCN17 [55], YrExp1 [17] and YrR212 [55] on 1BL. Furthermore several stripe rust resistance QTL have been mapped to chromosome 1B including: QYr.sun-1B [56], QPST.jic-1BL [57] and a QTL linked to Xgwm259 [58].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, adultplant resistance to stripe rust controlled by a single gene or QTL was reported in wheat genotypes "Bersee" as Yr16 [61], in "Pavon F76" as Yr29 [62], in wheat genotype "Lgst. 79 -74" as Yrns-B1 [63], in "Opata 85" as Yr30 [64], in "Cook" [65], in a T. boeoticum transgressed wheat genotype as QYrtb.pau-5A and a T. monococcum transgressed wheat line as QYrtm.pau-2A [66], and in wheat genotype "Aquileja" [21]; and by three genes or QTL was reported in "Guardian" [67]. In winter wheat "IDO444", HTAP resistance is controlled by two major QTL and three minor QTL [56].…”
Section: Genetics Of Htap Resistancementioning
confidence: 99%